FORMING A CUSTOMER-ORIENTED MODEL OF RESTAURANT SERVICE WITH A FOCUS ON QUALITY, FOOD TRADITIONS, AND CONSUMER EXPECTATIONS (Development Service Industry Management, 2025)
The article explores the essence of customer orientation as a crucial factor in improving the quality of service in the hotel and restaurant industry. It analyzes modern approaches to shaping the customer experience based on the integration of principles from service marketing, consumer psychology, quality management, and digital technologies. Special attention is given to the implementation of personalized services, the development of employees' emotional intelligence, and the use of consumer data analytics for flexible response to their expectations. The significance of a customer-oriented approach as a component of the competitiveness of hospitality establishments is revealed. Examples of innovative customer interaction practices are presented, including the use of online platforms, feedback systems, gamification, and social media. The importance of forming a service culture based on trust, respect for the customer, and continuous improvement of service standards is substantiated. The article concludes on the advisability of a systematic approach to implementing customer orientation as a strategic direction for the development of hospitality enterprises amid a dynamic market and growing competition.
Keywords: customer-oriented approach; service quality; hotel and restaurant business; service culture; customer loyalty; multicultural service; customer experience